PERANAN JOB ORDER COSTING METHOD DALAM MENENTUKAN HARGA POKOK PRODUKSI (STUDI KASUS PADA CV. TRINITY MANADO) - Runtu, Jessica Graziella Whitney; Poputra, Agus; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Job order costing is a system that collects product costing and charge to a specific job. Job order costing system is used for companies that produce a veriety of products during certain periods and costs are calculated individually for each job. This study aimed to analyze use job order costing method in determining the production cost on a CV. Trinity Manado. Methods of data analysis used this research is descriptive qualitative research method, where the study was conducted by collecting data and analyze the collected data and provide information. Authors collected data using techniques of documentation and interviews. Based on the research, imposition the factory overhead costs that do CV. Trinity is not quite right. CV. Trinity only imposes an element of overhead costs such as the costs of helper only while electricity costs are not included in the factory overhead cost. Key Word: job order costing, the production cost, factory overhead cost